Properties of Cementitious Composites Mixing Perlite and Carbonized Cork (Architecture Image Studies, 2025)
In this study, a cementitious composite was fabricated using perlite and carbonized cork, which are eco-friendly lightweight aggregates, and its physical properties and fire stability performance were analyzed. The objective of the study was to examine the mechanical strength and thermal insulation performance of perlite and carbonized cork, as well as to evaluate their pollutant adsorption performance for improving indoor air quality in buildings. Experimental results showed that as the mixing ratio of perlite and carbonized cork increased, the compressive and flexural strengths of the cementitious composite generally decreased. In particular, the reduction in strength was more significant when carbonized cork was used compared to perlite. Meanwhile, as the proportion of perlite increased, the pollutant adsorption performance improved, although the thermal insulation performance decreased slightly. Conversely, increasing the proportion of carbonized cork led to a decrease in adsorption performance but showed a tendency to improve thermal insulation. Through comprehensive experimental analysis, the optimal mixing ratio of carbonized cork to perlite was determined to be 3:2, suggesting that the proposed cement cementitious composite can contribute to improving both indoor air quality and the thermal insulation performance of buildings.